Nanoparticulate Drug Delivery System of Geriforte - V, Maruthappan (Journal of Medical Biomedical and Applied Sciences, 2016)
The aim of the study Geriforte loaded Eudragit nanoparticles were prepared and targeted to various organs to a satisfactory level. Re-cent research on idealizing drug delivery systems which is progressing at a prodigious rate, aims at the development of drug delivery systems with maximum therapeutic benefits of drug delivery thus resulting in safe and effective management of diseases. Nanoparti-culate drug delivery system for Geriforte was developed, that would overcome the therapeutic risks of conventional formulations and was evaluated with respect to particle size, drug content, in vitro release and in vivo targeting. Geriforte is used to proven antistress adaptogenic, comprehensive, systemic and metabolic corrective. The commercially available formulations of Geriforte are associated with acute hemodynamic changes that result in nephrotoxicity and also have low bioavailability. Geriforte (GER) loaded Eudragit RL 100 nanoparticles were prepared using solvent evaporation technique, with 2% PVA as stabilizer. Three batches of nanoparticles with varying drug concentrations (GER-1, GER-2 and GER-3) were prepared. Cumulative % drug release of formulations GER-1, GER-2 and GER-3 was 91.25%, 90.79% and 85.18% respectively. Formulation GER-2, which proved to be the best showed a mean particle size of 232 nm and entrapment efficiency of 55.17%. The in vivo result of formulation GER-2 revealed that the drug loaded nanoparticles showed preferential drug targeting to liver followed by spleen and kidneys.ÃÂ